2021
DOI: 10.1111/jocn.15655
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and unit variables of missed nursing care in acute care hospitals: A cross‐sectional study

Abstract: Aims and Objectives To investigate hospital, unit and staff variables as the correlates of missed nursing care (MNC) in Czech hospitals. Background There is a considerable variability in patterns of MNC across different hospital, unit and staff characteristics. Design A cross‐sectional study was conducted. The STROBE guidelines for reporting observational studies were followed for reporting of the research study. Methods A sample of 513 nurses working in nine acute care hospitals was recruited. MNC activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 36 publications
(99 reference statements)
6
16
1
2
Order By: Relevance
“…Study findings show that MNC occurred in all categories of nursing care. The patterns and reasons of MNC revealed in this study were in line with previous studies in the Czech Republic (Jarošová et al, 2021;Zeleníková et al, 2019Zeleníková et al, , 2020aZeleníková et al, , 2020b and other European studies (Bragadóttir et al, 2017;Palese et al, 2015;Bagnasco et al, 2020) based on the missed care approach and conducted before the COVID-19 pandemic. In line with our results, a Swedish comparative study (von Vogelsang et al, 2021) revealed similar levels and reasons of MNC before and during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Study findings show that MNC occurred in all categories of nursing care. The patterns and reasons of MNC revealed in this study were in line with previous studies in the Czech Republic (Jarošová et al, 2021;Zeleníková et al, 2019Zeleníková et al, , 2020aZeleníková et al, , 2020b and other European studies (Bragadóttir et al, 2017;Palese et al, 2015;Bagnasco et al, 2020) based on the missed care approach and conducted before the COVID-19 pandemic. In line with our results, a Swedish comparative study (von Vogelsang et al, 2021) revealed similar levels and reasons of MNC before and during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…b Subscales of the PES-NWI NFQoC -"Nursing Foundations for Quality of Care", NPHA -"Nurse Participation in Hospital Affairs", SRA -"Staffing and Resource Adequacy" 2020), and therefore there is less capacity to mitigate the frequencies of MNC during the pandemic. However, the prevalence of MNC in this study was not higher in comparison with recent studies conducted in Czech acute care settings before the COVID-19 pandemic (Jarošová et al, 2021;Zeleníková et al, 2021). Study findings show that MNC occurred in all categories of nursing care.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations